Pengaruh Knowledge, Psychological Empowerment, dan Work Experience Terhadap Kinerja SDM Pada UMKM Batik Tulis Tanjung Bumi: Pengaruh Knowledge, Psychological Empowerment, dan Work Experience Terhadap Kinerja SDM Pada UMKM Batik Tulis Tanjung Bumi - Baruno, Agustiawan; Bharmawan, Agus Surya; Hidayat, Wahyu (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS DR SOETOMO SURABAYA, 2023)
Micro, Small and Medium Enterprises are one of the business groups that can survive the most when the economic crisis hits this country. The development of the number of UMKM units continues to increase, of course it will be able to open up greater job opportunities. However, this small business is still seen as a business with weak performance. To overcome good performance, of course, UMKM businesses require the development of quality human resources. Quality improvement is needed, especially in the field of knowledge, Psychological Empowerment, and work experience in entrepreneurship. This study aims to analyze the effect of knowledge, Psychological Empowerment, and work experience on human resource performance at the UMKM Batik Tulis Tanjung Bumi. In this study, researchers used associative research methods with causal relationships using a quantitative approach. With a population of 40 respondents with sampling using the saturated sampling method. The results of this study indicate that the independent variable contributes to the dependent variable 70.9%. By showing the F test of knowledge, Psychological Empowerment, and work experience variables with the results of F arithmetic > F table, namely 32.668 > 3.25 which explains the positive and significant influence on human resource performance. A t test of the knowledge variable on human resource performance was carried out with the results of t arithmetic > t table that was 2,078 > 2,028 and a prob Psychological Empowerment value of 0.045 < 0.05, the Psychological Empowerment variable on human resource performance with the results of t arithmetic > t table that was 3.784 > 2.028 and a prob Psychological Empowerment value of 0.001 < 0.05, the same thing is also obtained that the work experience variable on human resource performance where the results are 3.226 > 2.028 and a probPsychological Empowerment value of 0.003 < 0.05, this indicates that each independent variable has a positive and significant effect on the dependent variable.